2021
DOI: 10.3390/membranes11110872
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design and Porosity of Porous Alumina Ceramic Membrane for Air Bearing

Abstract: Air bearing has been widely applied in ultra-precision machine tools, aerospace and other fields. The restrictor of the porous material is the key component in air bearings, but its performance is limited by the machining accuracy. A combination of optimization design and material modification of the porous alumina ceramic membrane is proposed to improve performance within an air bearing. Porous alumina ceramics were prepared by adding a pore-forming agent and performing solid-phase sintering at 1600 °C for 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the improvement of air bearing, a combination of design optimization and porous alumina material design has been attempted. A restrictor material composed of porous alumina ceramic membrane was manufactured by using polystyrene microspheres as pore‐forming agent (PFA) and it was reported that an optimized porosity and mechanical response was achieved with a ceramic membrane of ∼12% porosity 15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the improvement of air bearing, a combination of design optimization and porous alumina material design has been attempted. A restrictor material composed of porous alumina ceramic membrane was manufactured by using polystyrene microspheres as pore‐forming agent (PFA) and it was reported that an optimized porosity and mechanical response was achieved with a ceramic membrane of ∼12% porosity 15 …”
Section: Introductionmentioning
confidence: 99%
“…A restrictor material composed of porous alumina ceramic membrane was manufactured by using polystyrene microspheres as pore-forming agent (PFA) and it was reported that an optimized porosity and mechanical response was achieved with a ceramic membrane of ∼12% porosity. 15 Typical conventional fabrication processes that are used in the production of porous ceramics are partial sintering, sacrificial fugitives, replica templates, direct foaming, sol-gel method, foam-gel casting, and freeze casting. 16 Although conventional methods are successful in production of porous ceramics with controlled porosity and pore size distribution, they have limitations in production of complex structures with sufficient structural integrity.…”
mentioning
confidence: 99%
“…Inorganic membrane has excellent properties such as robustness, physicochemical stability, and long-term performance. Jianzhou Du et al [ 1 ] prepared porous alumina ceramic membranes on air bearings. The results showed that the load capacity increased from 94 N to 523 N when the porosity increased from 5% to 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Special measures for depositing thin films on Si 3 N 4 reduce wear. Diamond films have excellent mechanical and tribological properties, such as high hardness, good wear resistance, and a low coefficient of friction, and have received extensive attention in mechanical and tribological, high-performance engineering surfaces [ 1 , 3 ]. Si 3 N 4 ceramic is considered an ideal material for the deposition of diamond films (~1 × 10 −6 K −1 ) due to its low thermal expansion coefficient (~2.9 × 10 −6 K −1 ), which ensures the required bonding strength between diamond films and substrates [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%